Pertunjukan Beralas Bumi Beratap Langit: Investigasi Keaktoran dan Ruang melalui Site-Specific - Abdur Rizky Akbar (Universitas Gadjah Mada, 2022)
Acting is considered as a way of art, the experience of acting placed as an aesthetic sublimation. The process can be seen from the development of the actor who was originally the subject of language turning into the subject of desire to become the subject of encouragement. Central to the Site-specific approach is a concern to the potential of unconventional spaces. The development of theatrical studies, particularly on actors and space, there seems to be little clarity on the parameters of this approach and it appears to have become a flexible term in which many manifestations have begun to accumulate. The Site-Specific approach seeks to use unique site landscape properties. Locations were chosen based on their ability to reinforce storytelling and form a clearer backgrounf for actors in a theatrical production. This paper aims to investigate a personalized Site-specific approach to performance interests in order to provide insight into the modes of acting and actors as subjects in theatrical performances. The practicality of the site-specific approach to the theater stage model resulted in the following conclusions: 1) natural sets create an atmosphere of intimacy, 2) help actors feel active immersion in the world that is being played, and 3) provide rich cultural visualizations that are relevant to the actor's image.